The role of information technology in the organization: a review, model, and assessment - Dewett, Todd; Jones, Gareth R. (Journal of Management, 2001)
This paper reviews and extends recent scholarly and popular literature to provide a broad overview of how information technology (IT) impacts organizational characteristics and outcomes. First, based on a review of the literature, we describe two of the principal performance enhancing benefits of IT: information efficiencies and information synergies, and identify five main organizational outcomes of the application of IT that embody these benefits. We then discuss the role that IT plays in moderating the relationship between organizational characteristics including structure, size, learning, culture, and interorganizational relationships and the most strategic outcomes, organizational efficiency and innovation. Throughout we discuss the limitations and possible negative consequences of the use of IT and close by considering several key areas for future research.